Electroacustimulation is as Effective as B6 for Reducing Nausea and Vomiting in the First Trimester of Pregnancy - Pamungkas, Novan S. (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To determine the benefit of electroacustimulation in reducing nausea and vomiting in the first trimester of pregnancy. Methods: This study is an experimental study. The subject were 40 pregnant women divided into 2 groups randomly. The control group was given vitamin B6 3x30 mg per day and the case given the electroacustimulation device. The degree of severity of nausea and vomiting of patients assessed before and 3 days after treatment using Pregnancy Unique Quantification of Emesis and Nausea (PUQE) questionnaire. Result: There were no differences between groups in gestational age at entry and PUQE score pre-treatment. After 3 days therapy, there were significant decrease in PUQE score in group receiving B6 (p=0.004) and also in electroacustimulation group (p=0.000). However, the change in PUQE score was not significantly different between the two groups (p=0.286). Conclusion: From the results of this study concluded that electroacustimulation is effective for reducing nausea and vomiting in the first trimester of pregnancy. There is no difference in effectiveness between electroacustimulation and vitamin B6 to treat nausea and vomiting in the first trimester of pregnancy. [Indones J Obstet Gynecol 2013; 37-2: 71-6] Keywords: electroacustimulation, nausea and vomiting in pregnancy, P6 or neiguan point, pregnancy unique quantification of emesis and nausea (PUQE)